Present and future isochronous mass spectrometry at GSI-FAIR : 25 new masses of fission fragments ; novel analysis method ; design of a new Time-of-Flight detector system - Diwisch, Marcel; Justus Liebig University Giessen (My University, 2015)
In this work the basic features of isochronous mass spectroscopy (IMS) for the present facilities at GSI and also for the future experiments at FAIR have been experimentally and theoretically investigated. The prospects and limitations of IMS have been carefully studied with calculations and experiments. The data of two different previous IMS experiments at GSI have been combined and analyzed with a novel correlation-matrix method (CMM). Both experiments were performed with the fragment separator FRS and the experimental ion storage ring ESR. In both experiments fission fragments, created by 238U projectiles in a beryllium target at the entrance of the FRS, were spatially separated and injected into the isochronous ESR. In the first experiment the full Brho acceptance of the ESR was used whereas in the second one the Brho of each fragment was defined by slits in the dispersive central focal plane of the FRS. In this way the magnetic rigidity was well-determined for all injected fragments to dBrho/Brho; = 1.5E-4. The harvest of this analysis is 25 new masses near and at the N=82 shell closure. The comparison of the experimental results with the AME extrapolation and different theoretical models reveal significant differences due to the low theoretical prediction power of the calculations in this mass range. In this respect one has to emphasize that due to the novel analysis method in this work these 25 new masses could be extracted additional to our previously already published results. It is almost needless to mention that the new mass values will contribute to improved r-process calculations which are in progress. In the present analysis the existing matrix method was extended with a variable scaling factor (s). The scaling factor was determined for each mass-to-charge ratio (m/q) of the measured ions and implemented as a function of m/q in the analysis. This has extended the accessible m/q range. The revolution time was determined via a 3rd-order fit of the time stamps at Nmax/2, where Nmax represents the maximum number of turns an individual ion has reached circulating in the ESR. Contrary to previous analysis works no restriction was applied and thus the most exotic nuclides with naturally low statistics were included here. The accuracy for the new mass values are about 180 keV which is mainly determined by the systematic error and the statistics. The performance of the ToF detector, the extraction of the time stamps, and the ion-optical properties determine the accuracy and limitation of IMS including CMM. These different contributions were investigated in the present work by systematic simulations and test experiments. A main result of these studies is that for ions that circulate 200 turns or more the present timing performance of the ToF detector has a minor influence on the possible mass accuracy but the ion-optics of the ring. MOCADI simulations with first- and third-order matrices clearly demonstrate the latter statement, especially for m/q values far from the isochronous ion. This result confirms previous publications that for IMS one has to measure the revolution time and independently the magnetic rigidity or the velocity. In future IMS experiments this requirement can be fulfilled with the new dual ToF detector system designed in the frame work of this doctoral thesis. The timing performance of the present ESR ToF detector has been substantially improved by increasing the electric field strength from 156 V/mm to 300 V/mm. This change has decreased the time spread from 45 ps to 35 ps. The results were obtained in simulations and verified in test experiments with alpha particles. The excellent agreement between measurements and simulations has been the basis for the design of the future dual time-of-flight detector system which will be installed in the Collector Ring of FAIR. The two ToF detectors will be installed about 22 m apart and allow a velocity determination of better than 10E-4 which is needed for accurate mass determination. The new ToF detector is a big challenge because the foil diameter has to be doubled compared to the present ESR detector. The increase in size is needed to match the much larger emittance of the stored fragment beam circulating in the CR. The diameter of the planned carbon foil is 80 mm and the geometrical dimensions of the detector are: 562 mm width, 180 mm height, and 236 mm length in beam direction. The design of the new detector was done and the performance investigated in systematic simulations. The excellent result is that despite of the much larger dimension of the detector the timing performance has even increased compared to the ESR detector. The validity of the results from the simulation programs has been tested by reproducing the measured data of the present ESR detector. In this sense we are confident that with the new dual ToF detector system IMS experiments have a large discovery potential especially for the very short-lived exotic nuclei that cannot be accessed by other experimental methods.
Gegenwärtige und Zukünftige Isochrone Massenspektrometrie an GSI-FAIR : 25 neue Massen aus Spaltfragmenten ; Neuartige Analysemethode ; Design eines neuen Flugzeitdetektorsystems
Keywords: ddc:530